Discrimination against Shia Minorities in Indonesia: A Human Rights Perspective - mohamad arafah idrus; Muhammad Muhammad; Muammar Bakri; Ratna Istianah (Sabtida, 2026)
Religious freedom is a fundamental human right guaranteed by the Constitution of Indonesia and international human rights instruments. However, discriminatory practices against religious minority groups remain a pressing challenge. The Shia community, as one of these minorities, has often faced social exclusion, stigmatization, restrictions on religious activities, and unequal treatment in public life. In Makassar, the presence of Shia organizations has frequently encountered resistance from certain segments of society. This study aims to analyze the process of discrimination against the Shia minority in Makassar, identify the forms of discrimination experienced, and examine government policies in addressing such issues. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observation, documentation, and literature review. Informants included Shia community leaders, religious leaders, academics, and government representatives, selected purposively. Data analysis followed the Miles and Huberman interactive model, consisting of reduction, display, and conclusion drawing. The findings reveal that discrimination against the Shia community is shaped by theological differences, identity politics, and institutional factors. It manifests in direct, indirect, and regulatory forms. Although legal frameworks exist to protect religious freedom, their implementation remains ineffective, creating a gap between constitutional guarantees and the lived realities of the Shia minority in Makassar